Power transitions and the rise of the regulatory state: Global market governance in flux. Issue 3 (3rd May 2021) - Lavenex, Sandra; Serrano, Omar; Büthe, Tim
Abstract: This special issue examines the consequences of the ongoing power transition in the world economy for global regulatory regimes, especially the variation in rising powers' transition from rule‐takers to rule‐makers in global markets. This introductory article presents the analytical framework for better understanding those consequences, the Power Transition Theory of Global Economic Governance (PTT‐GEG), which extends the scope of traditional power transition theory to conflict and cooperation in the international political economy and global regulatory governance. PTT‐GEG emphasizes variation in the institutional strength of the regulatory state as the key conduit through which the growing market size of the emergent economies gives their governments leverage in global regulatory regimes. Whether or not a particular rising power, for a particular regulatory issue, invests its resources in building a strong regulatory state, however, is a political choice, requiring an analysis of the interplay of domestic and international politics that fuels or inhibits the creation of regulatory capacity and capability. PTT‐GEG further emphasizes variation in the extent to which rising powers' substantive, policy‐specific preferences diverge from the established powers' preferences as enshrined in the regulatory status quo. Divergence should not be assumed as given. Distinct combinations of these two variables yield, for each regulatory regime, distinct theoretical expectations about how the power transition in the world economy will affect global economic governance, helping us identify the conditions under which rule‐takers will become regime‐transforming rule‐makers, regime‐undermining rule‐breakers, resentful rule‐fakers, or regime‐strengthening rule‐promoters, as well as the conditions under which they remain weakly regime‐supporting rule‐takers.